Design of machinery : an introduction to the synthesis and analysis of mechanisms and machines / [cakera padat] - 209109 Norton, Robert L. (Boston : WCB/McGraw-Hill, 1999)
System requirements: Windows 95 or NT 4.0 or later; or MacOS 7.1 or higher